Barrier Properties and Transcriptome Expression in Human iPSC-Derived Models of the Blood–Brain Barrier. (5th November 2018) - Delsing, Louise; Dönnes, Pierre; Sánchez, José; Clausen, Maryam; Voulgaris, Dimitrios; Falk, Anna; Herland, Anna; Brolén, Gabriella; Zetterberg, Henrik; Hicks, Ryan; Synnergren, Jane
Abstract : Cell-based models of the blood–brain barrier (BBB) are important for increasing the knowledge of BBB formation, degradation and brain exposure of drug substances. Human models are preferred over animal models because of interspecies differences in BBB structure and function. However, access to human primary BBB tissue is limited and has shown degeneration of BBB functions in vitro. Human induced pluripotent stem cells (iPSCs) can be used to generate relevant cell types to model the BBB with human tissue. We generated a human iPSC-derived model of the BBB that includes endothelial cells in coculture with pericytes, astrocytes and neurons. Evaluation of barrier properties showed that the endothelial cells in our coculture model have high transendothelial electrical resistance, functional efflux and ability to discriminate between CNS permeable and non-permeable substances. Whole genome expression profiling revealed transcriptional changes that occur in coculture, including upregulation of tight junction proteins, such as claudins and neurotransmitter transporters. Pathway analysis implicated changes in the WNT, TNF, and PI3K-Akt pathways upon coculture. Our data suggest that coculture of iPSC-derived endothelial cells promotes barrier formation on a functional and transcriptional level. The information about gene expression changes in coculture can be used to further improve iPSC-derived BBB models through selective pathway manipulation. Abstract : Human induced pluripotent stem cells (iPSCs) can be used to generate relevant cell types to model the BBB with human tissue. We generated a human iPSC-derived model of the BBB that includes endothelial cells in coculture with pericytes, astrocytes, and neurons. Evaluation of barrier properties and whole genome transcription analysis showed improved BBB modeling in the cocultures. Cocultured endothelial cells have high transendothelial electrical resistance, functional efflux, ability to discriminate between CNS permeable and nonpermeable substances and upregulation of brain specific transporters.